Ketahanan Padi Transgenik DB1 terhadap Penggerek Batang Padi Kuning Scirpophaga incertulas Walker (Lepidoptera: Pyralidae) - Nono Carsono; Irma Mangatur; Fitri Utami Hasan; Santika Sari; Nenet Susniahti; Hersanti Hersanti; Baehaki S.E. Baehaki S.E. (Fakultas Pertanian Universitas Padjadjaran, 2017)
ABSTRACTResistance of DB1 transgenic rice to the yellow rice stem borer (Scirpophaga incertulas Walker) (Lepidoptera: Pyralidae)Decrease in rice production in Indonesia can be fulfilled by improving quality and quantity of rice. Rice stem borer (Scirpophaga incertulas) is an important pest that considered being detrimental to rice. The aim of this study was to determine resistance level of DB1 transgenic rice which compared to cv. Taichung-65 (wild-type), Ciherang and IR64 to the pest. Experiments were arranged in Completely Randomized Design and Randomized Block Design. The result showed that DB1 transgenic rice, Taichung-65, IR64 and Ciherang were susceptible with scale 9. The mortality of DB1 transgenic rice was not significantly different with Taichung-65, IR64 and Ciherang. The low levels of resistance in DB1 transgenic rice, Taichung-65, IR64 and Ciherang were also seen in development and growth time of S. incertulas. There was no disruption on development and growth of S. incertulas. DB1 genes were still not enough to provide maximum resistance to S. incertulas and still need to discover information of other genes that can be inserted and increase the resistance of rice to S. incertulas.Keywords: Transgenic rice, DB1 transgene, Yellow rice stem borerABSTRAKSerangan hama telah menurunkan produksi beras, salah satu hama utama di Indonesia adalah penggerek batang padi kuning (Scirpophaga incertulas). Penelitian ini bertujuan untuk mengetahui tingkat ketahanan padi transgenik DB1 dibanding dengan padi Taichung-65 (padi originnya), Ciherang dan IR64 terhadap penggerek ini. Pada penelitian ini dilakukan pengujian tingkat ketahanan terhadap S. incertulas pada padi yang diuji. Percobaan ditata dengan Rancangan Acak Lengkap dan Rancangan Acak Kelompok. Hasil penelitian menunjukkan bahwa padi transgenik DB1, Taichung-65, IR64 dan Ciherang tergolong padi berketahanan rentan dengan skala 9. Mortalitas padi transgenik DB1 tidak berbeda nyata dengan padi Taichung-65, IR64 dan Ciherang. Rendahnya tingkat ketahanan pada padi transgenik DB1, Taichung-65, IR64 dan Ciherang juga terlihat pada lama perkembangan dan pertumbuhan S. incertulas yang relatif sama, tidak tampak gangguan perkembangan dan pertumbuhan S. incertulas. Gen DB1 masih belum cukup untuk memberikan ketahanan maksimal terhadap S. incertulas. Perlu dicari sumber gen lain guna meningkatkan ketahanan tanaman padi terhadap S. incertulas.Kata Kunci: Padi transgenik, Gen DB1, Penggerek batang padi kuning